Wind turbine doubly-fed asynchronous machine diagnosis defects using stator and rotor currents lissajous curves - Fatima El Hammouchi; L. El Menzhi; A. Saad; Y. Ihedrane; B. Bossoufi (Institute of Advanced Engineering and Science, 2019)
In the current paper, a method is developed to diagnose potential electrical defects attacking doubly fed induction generator in Moroccan wind turbines firms. The proposed method is based on stator and rotor currents Lissajous curves analysis. Firstly, we focus on modeling of a non-defected wind conversion systems based on mathematic model created in Matlab Simulink which is able to reflect the behaviour of the wind turbine during asynchronous generator defects-free operation. After that, an indirect stator field vector oriented control is applied to obtain the wind system performance. Finally, stator and rotor currents Lissajous curves are analyzed in case of a non-defected generator that represents the system reference curves for diagnosing defects. The simulations had been realized by Matlab Simulink. Their results showed the effectiveness of the proposed method.